MARKET EXPLORATION OF BAKSO CULINARY TOURISTS IN MALANG CITY, INDONESIA - Ahmadintya Anggit Hanggraito (Bahasa Indonesia, 2021)
Bakso is one of the top Indonesian local culinary from Malang City. This study tries to reveals types of food-related behaviour and culinary experiences in psychographic segmentation for bakso culinary tourism in Malang City. In addition, identifying the motivational factors of Bakso Malang tourists is useful for the development of culinary tourism. This study involved 210 samples and the results represented an exploration of market segmentation and motivation factors of bakso culinary tourists. That could be an in-depth consideration of the bakso restaurant even for culinary development strategies in Malang City. Bakso Malang's consistent understanding of market management will provide important intangible capital for the development of culinary products in Malang City.